P‐13.6: The Improvement of OLED Image Sticking Based on Motion Detection. (28th November 2018) - Sun, Chunlai; Fan, Rui; Wang, Hengjie; Zhang, Xiaoning; Hwang, Taijun; Wang, Limin
Abstract : An improvement method of OLED image sticking based on motion detection without additional circuit units is proposed. Images are divided into static images, mixed images, and moving images by comparing the image luminance among different frames. In this method, the static image is moved and its luminance is reduced. As for the mixed image, its luminance is reduced by varying proportions in different areas. When it is a moving image, the luminance of pixels is reduced. The simulation results show that the improvement can effectively improve OLED image sticking by using the image sticking evaluation method proposed. As for static images, the improvement percentage is 55.05%. When it comes to mixed images, the improvement in static areas is 14.29% and it is 3.29% in motion areas. As for moving images, the improvement percentage is 7.35%.